Heritable disorders of connective tissue: Description of a data repository and initial cohort characterization. Issue 4 (1st February 2019) - Bascom, Rebecca; Schubart, Jane R.; Mills, Susan; Smith, Thomas; Zukley, Linda M.; Francomano, Clair A.; McDonnell, Nazli
Abstract : We describe a data repository on heritable disorders of connective tissue (HDCT) assembled by the National Institutes of Health's National Institute on Aging (NIA) Intramural Research Program between 2001 and 2013. Participants included affected persons with a wide range of heritable connective tissue phenotypes, and unaffected family members. Elements include comprehensive history and physical examination, standardized laboratory data, physiologic measures and imaging, standardized patient‐reported outcome measures, and an extensive linked biorepository. The NIA made a commitment to make the repository available to extramural investigators and deposited samples at Coriell Tissue Repository ( N  = 126) and GenTAC registry ( N  = 132). The clinical dataset was transferred to Penn State University College of Medicine Clinical and Translational Science Institute in 2016, and data elements inventoried. The consented cohort of 1, 009 participants averaged 39 ± 18 years (mean ±  SD, range 2–95) at consent; gender distribution is 71% F and 83% self‐report Caucasian ethnicity. Diagnostic categories include Ehlers–Danlos syndrome (classical N  = 50, hypermobile N  = 99, vascular N  = 101, rare types and unclassified N  = 178), Marfan syndrome ( N  = 33), Stickler syndrome ( N  = 60), fibromuscular dysplasia ( N  = 135), Other HDCT ( N  = 72). Unaffected family members ( N  = 218) contributed DNA for the molecular archive only. We aim to develop further discrete data from unstructured elements, analyze multisymptom HDCT manifestations, encourage data use by other researchers and thereby better understand the complexity of these high‐morbidity conditions and their multifaceted effects on affected persons.